Opportunities and Specifics Underlying Day Care for Older Adults in Hungary with Consideration of Active Ageing - Vajda, Kinga (European Journal of Mental Health, 2020)
In the past few decades, ageing has become a serious global issue. The concept of active agingand its incorporation into different type of social services (e.g. day care for elderly people) is oneof the possible solutions. The main goal of this research was to evaluate the status of clients inHungarian day care institutions. Another important goal is to explore which domains of the conceptof active and independent ageing were already considered and applied in Hungarian day careservice and where they should be strengthened. The questionnaire was based on the Active AgeingIndex questionnaire (ZAIDI et al. 2013). 14% of the observed sample was 64 years old oryounger, 38% was 65–74 years old, 36% was 75–84 years old, 12% was 85 years old or older.Most of the participants (74%) were women. More than half of the sample were widowed. Onethird of the sample received some kind of ICT (Information and Communication Technology)device. There was a strong connection between the frequency of ICT usage and education variables.Accessibility, which was also a facilitator of active and independent ageing, came up onlyin 25% of the sample. Mental well-being – as a new variable – was analyzed with principle componentanalysis from five former variables with the highest rate in the Central Hungarian region.Satisfying physical security was reported by only 56% of the sample, more often among men (p= 0.03). Reinforcing the preventive aspect of the service, propagating it amongst freshly retiredpeople, and including not only widows, but other potential clients as well could be the key pointsof service development. To intensify the potential points in the service connected to active ageing(accessibility, volunteering in late-life, use of ICT devices etc.) could be a key factor in theimprovement of day care services..